GRS 1758–258: RXTE Monitoring of a Rare Persistent Hard State Black Hole - M. Obst; K. Pottschmidt; A. Lohfink; J. Wilms; M. Böck; D. M. Smith; J. A. Tomsick; I. Kreykenbohm (Acta Polytechnica, 2011)
GRS 1758–258 is the least studied of the three persistent black hole X-ray binaries in our Galaxy. It is also one of only two known black hole candidates, including all black hole transients, which shows a decrease of its 3-10 keV flux when entering the thermally dominated soft state, rather than an increase.We present the spectral evolution of GRS 1758–258 from RXTE-PCA observations spanning a time of about 11 years from 1996 to 2007. During this time, seven dim soft states are detected. We also consider INTEGRAL monitoring observations of the source and compare the long-term behavior to that of the bright persistent black hole X-ray binary Cygnus X-1. We discuss the observed state transitions in the light of physical scenarios for black hole transitions.